2014
DOI: 10.1266/ggs.89.61
|View full text |Cite
|
Sign up to set email alerts
|

A role for <i>TRIANGULAR HULL1</i> in fine-tuning spikelet morphogenesis in rice

Abstract: The lemma and palea, which enclose the pistil, stamens, and lodicules, are the most conspicuous organs in the rice spikelet. We isolated a mutant line (ng6569) in which the lemma and palea were narrower than those of the wild type, and found that the mutant had a defect in TRIANGULAR HULL1 (TH1), which encodes a nuclear protein with an ALOG domain. Detailed morphological analysis indicated that the th1 mutation caused a reduction in the size of tubercles, which are convex structures on the surface of the lemma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Meanwhile, in the th1 mutants, the marginal region of palea (mrp) looks normal and the alterations are due to shape changes of the lemma and the rest of palea (body of palea, bop) 36 . In addition, the lodicules of th1 florets were elongated and green 34 , 36 , 37 . Further observations showed that the surface of elongated lodicules was rough, crumpled and possessed some protrusions that were similar with those in the wild type hulls 36 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Meanwhile, in the th1 mutants, the marginal region of palea (mrp) looks normal and the alterations are due to shape changes of the lemma and the rest of palea (body of palea, bop) 36 . In addition, the lodicules of th1 florets were elongated and green 34 , 36 , 37 . Further observations showed that the surface of elongated lodicules was rough, crumpled and possessed some protrusions that were similar with those in the wild type hulls 36 .…”
Section: Discussionmentioning
confidence: 98%
“…In our study, the th1 mutation only resulted in a slight change in the shape of the lemma and palea. SEM observation of early stages of floret development in several allelic mutants of TH1 , such as bls1-1 and afd1 , showed that TH1 does not function at stages of floral-organ initiation and patterning but is required for lateral development of the lemma and palea in the final stages 34 – 36 . Our observation that TH1 controls cell size during the lateral development of lemma and palea is consistent with previous finding that TH1 is not associated with meristem function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, mutations in the closest homolog of TMF in rice simplifies panicle architecture (Yoshida et al 2013), but loss of the closest homologs in Arabidopsis (LIGHT-SENSITIVE HYPOCOTYL3 and LIGHT-SENSITIVE HYPOCOTYL4) has no effect on inflorescences, although overexpressing these genes suppresses lateral organ differentiation (Takeda et al 2011). A handful of other ALOG genes in Arabidopsis and rice have reported roles in light signaling and floral organ development (Zhao et al 2004;Yoshida et al 2009;Cho and Zambryski 2011;Takeda et al 2011;Sato et al 2014). Thus, ALOG proteins represent a new, poorly understood family of growth regulators with prominent, species-specific roles in reproductive development.…”
mentioning
confidence: 99%
“…For example, the DEPRESSED PALEA1 (DP1) gene encoding an AT-hook DNA binding protein regulates proper development of the central region of the palea (Jin et al, 2011), whereas the G1 gene encoding a plant-specific nuclear factor specifies sterile lemma identity by repressing lemma identity . The TRIANGULAR HULL1 (TH1) gene, belonging to the same gene family as G1, is involved in structural fine-tuning of the lemma and palea (Sato et al, 2014). Although Arabidopsis has homologs of these genes, there is no report that they are involved in flower development in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%